Pandangan generasi muda terhadap upacara perkawinan adat di Kota Ujungpandang - Pertiwi, Wiwik; Subagyo, Wisnu (Jakarta : Departemen Pendidikan dan Kebudayaan, 1998)
Attitude toward traditional marriage among the youth in Ujung Pandang, Sulawesi Selatan Province.
Includes bibliographical references (p. 129-130).
Keywords: Marriage customs and rites -- Indonesia -- Makassar; Youth -- Indonesia -- Makassar -- Attitudes